ANALISIS TERHADAP PENGERTIAN ORANG LAIN PEMANGKU JABATAN NOTARIS DALAM KETENTUAN PASAL 3 AYAT (3) KODE ETIK NOTARIS KAITANNYA DENGAN KEWAJIBAN NOTARIS DALAM PASAL 16 AYAT (1) HURUF (A) UNDANG-UNDANG JABATAN NOTARIS - Ferika Pramitha Mulyani (Universitas Sriwijaya, 2015)
Abstract : A law must contain a clear and complete formulation to avoid various interpretations. In relation to Article 3 Paragraph (3) of the Code of conduct of the Notary with Article 82 No. 30 of 2004 concerning the Notary as amended by Act No. 2 of 2014, states that the Notary shall take shelter in an organization that Indonesian Notaries Association (I.N.I). The Code of Conduct is a moral code. The Legal issues in this thesis, namely the provisions of the Code of conduct of the Notary mentions the word of another person who hold and run up the position of public Notary. This means that another person besides the public Notary who can hold the position of Public Notary. Whoever the another person, what criteria of another person and what sanctions that may be imposed on such another person when making a mistake and violate the Code of Conduct and Law of Public Notary, and how when the same material is set out in the Code of Conduct as a norm of conduct and UUJN as legal norms, then what kind of the norm, whether included in the ethical norms, legal norms or both that norms of ethics and legal norms. This type of research of this thesis is a normative legal research, which forms the legal research conducted by examining the law material of secondary data by the method of approach to philosophy, law and conceptual approaches, and techniques concluding with the deductive method. Based on the research results can be concluded another person referred to in the Code of Conduct is the Substitute of Public Notary and Interim Public Notary also applies to it all the provisions applicable to the Notary. Another person can also be checked and sentenced for the violations and mistakes he was done.Keywords: the Public Notary, Another Person, the Code of conduct